Reverse logistics and corporate performance: Cases studies in Brazilian companies - Hernández, Cecilia T.; Marins, Fernando A.S. [UNESP]; Castro, Roberto C.; Duran, Jorge A.R.; Salomon, Valerio A.P. [UNESP] (My University, 2013)
In the last few years Reverse Logistics (RL) activities are gaining importance in Brazilian companies. However, a relevant problem is to identify how different Reverse Logistics programs can affect corporate performance indicators. These situations can be treated as being Multi-Criteria Decision-Making (MCDM). In this work we adopted the Analytic Network Process (ANP) as the analytical technique of a MCDM problem that can be formulated when we have interest in to identify existing relationships between RL Programs and corporate performance. Here we present an analysis of sustainable practices identified in companies that belong to the automotive and publishing branches, operating in Brazil. The results indicated that ANP is an adequate method. The managers consulted validated the results, and they were compatible with the reality of the Brazilian companies.
Keywords: Analytic network process; Brazilian study case; Corporate performance; Multi-criteria decision-making problems; Reverse logistics